2020
DOI: 10.1111/aej.12460
|View full text |Cite
|
Sign up to set email alerts
|

Calcium hydroxide paste removal strategies and bond strengths of epoxy‐ and silicate‐based sealers

Abstract: This study evaluated the syringe/needle (SN), passive ultrasonic irrigation (PUI) and XP‐endo Finisher (XP) in the removal of Ca(OH)2‐based paste and the bond strength (BS) values of an epoxy resin (AH Plus) and silicate (MTA)‐based sealers to root dentin. Eighty lower premolars were assigned: control group (CT), SN, PUI and XP, and subdivided according to the sealer (n = 10) for BS. SN has the lowest removal followed by PUI and XP. AH Plus had higher BS for CT compared with SN in all root thirds. CT and XP pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… 1 Moreover, Ca(OH) 2 resides might prevent the penetration of sealers into dentinal tubules and provide a reduction in bond strength values of epoxy resin AH Plus (Dentsply Sirona, Konstanz, Germany). 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Moreover, Ca(OH) 2 resides might prevent the penetration of sealers into dentinal tubules and provide a reduction in bond strength values of epoxy resin AH Plus (Dentsply Sirona, Konstanz, Germany). 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of XP-endo Finisher in the removal of Ca(OH) 2 intracanal medicament have been investigated in premolar teeth, simulated internal resorption cavities, and artificial standardized groove. 3 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies evaluating the removal of calcium hydroxide from root canal irregularities. These studies have shown that irrigation agitation techniques remove more calcium hydroxide than CSI [22][23][24]. However, few studies have evaluated the removal of AH plus and CSBS from root canals by using irrigation agitation systems [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Due to different setups and study designs it is not easy to compare certain results between studies. Most studies, however, have in common that they observed difficulties in removing all remnants of CH from root canals [18,19,[25][26][27][28]. Only few studies showed a complete removal [29].…”
Section: Discussionmentioning
confidence: 99%
“…resolution of a sinus tract) or during specific endodontic procedures, such as apexification [12][13][14][15]. Prior to final root canal obturation, however, CH should be fully removed again, because remnants can prevent sealer penetration into dentinal tubules and negatively influence sealing ability and bond strength [16][17][18]. It has been shown, that even in straight single rooted teeth, a standard Syringe Irrigation (SI) technique is not capable of removing CH completely [19].…”
Section: Introductionmentioning
confidence: 99%